Edukasi Dini Pajak kepada Calon Wajib Pajak - Suparmin; Satiman; Edon Ramdani (Universitas Pamulang, 2025)
The largest component of state revenue is the tax sector. Tax revenue contributed 82.1% to Indonesia's state revenue in 2024, up from approximately 77.5% the previous year. Taxes are the foundation of the modern state's mutual assistance system. Without tax contributions, the state would lose its primary means of providing basic services to its citizens. The Ministry of Finance noted that by the first semester of 2025, tax revenue had reached IDR 1,420 trillion, or approximately 58% of the annual target. However, on the other hand, untapped tax potential remains enormous. Research shows that Indonesia's tax gap still ranges from 6–9% of gross domestic product (GDP), meaning approximately IDR 1,300 trillion in potential taxes are lost annually due to non-compliance and an untapped informal sector. If this situation is allowed to continue, the country will experience a widening fiscal deficit, forcing the government to borrow more or cut public services. It is very difficult to achieve voluntary taxpayer awareness and concern if the definition of